Pain catastrophizing: rumination is a discriminating factor among individuals with different pain characteristic - Bonafé, Fernanda Salloumé Sampaio (2019)
The objective of this study was to compare the scores of the Helplessness, Magnification, Rumination, and Catastrophizing factors of the Pain Catastrophizing Scale (PCS) between samples with different pain characteristics. The psychometric properties of the PCS were evaluated in 1,151 Brazilian adults (78.9% female; 38.6 (SD = 10.8) years): 335 had no pain, 390 had been in pain for less than 3 months, 250 had been in recurring pain for more than 3 months, and 176 had been in continuous pain for more than 3 months. Confirmatory factor analysis (CFA) was conducted to verify the fit of the PCS models. Convergent validity and reliability were evaluated. Multi-group analysis was used to estimate the invariance of the factorial model. The global score for the PCS factors was obtained using the regression weight matrix for estimating factor scores from CFA. Analysis of variance was used to compare scores between samples. After excluding three items, the tri-factorial model showed adequate fit. The model parameters were invariant (Δχ2(λ,i,β,Res); p≥0.05). Individuals experiencing pain showed higher scores for catastrophic thoughts. Individuals with pain for less than 3 months had the highest scores for Rumination (p < 0.001). The PCS showed valid, reliable, and invariant results for the sample of Brazilian adults in no pain or with different pain conditions. The PCS adequately discriminated individuals in pain from those without pain. Among those in pain, Rumination was the only discriminating factor.